Arrhythmic episodes in patients implanted with a cardioverter-defibrillator – results from the Prospective Study on Predictive Quality with Preferencing PainFree ATP therapies (4P) - François Regoli; Denis Graf; Beat Schaer; Firat Duru; Peter Ammann; Lorenza Mangoni di S. Stefano; Barbara Naegli; Haran Burri; Rainer Zbinden; Nazmi Krasniqi; Martin Fromer; 4P Study Group (BMC Cardiovascular Disorders, 2019)
Abstract Background Little is known about the ICD performance using enhanced detection algorithms in unselected, non-trial patients. Performance of recent generation ICD equipped with SmartShock™ technology (SST) for detection and conversion of ventricular tachyarrhythmias (VTA) was investigated. Methods 4P was a prospective, multicenter, observational study conducted in 10 Swiss implanting centers. Patients with a Class I indication according to international guidelines were included and received an ICD with SST. ICD discrimination capability was assessed by evaluating SST performance; therapy efficacy was assessed by rate of VTA conversions by ATP and by rescue shocks. Results Overall, 196 patients were included in the analysis with a mean duration of follow-up of 27.7 months (452 patient-years of observation). Patient-specific rather than recommended programming was preferred. Device-detected episodes were frequent (5147 episodes in 146 patients, 74.5%). In 44 patients (22.4%), 1274 episodes were categorized as VTA; only 215 episodes were symptomatic. ATP was the first-line therapy and highly effective (99.9% success rate at the episode level, 100.0% at the patient level). Rescue shocks were rare (66 episodes in 28 patients); 7 shocks in 5 patients (2.6%) were inappropriate. Death and hospitalization rates were low. Conclusions In a cohort of non-trial, unselected ICD patients, VTA episodes were frequent. The 4P results confirm the robustness of VTA detection by SST and the effectiveness of ATP treatment, hence limiting overall ICD shock burden.